QRIS Adoption Among Gen Z: Does Hedonic Lifestyle Matters? - Pratiwi, Ashfi (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This study examines the effect of Digital Financial Literacy on QRIS Usage moderated by Hedonic Lifestyle in Gen-Z Solo Raya. This research uses a quantitative approach. Through purposive sampling technique, 100 respondents from 5 districts and 1 city in Solo Raya were selected for this study. Data was collected through a Google Form questionnaire. The data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that there is a positive and significant influence between Digital Financial Literacy and QRIS Usage among Gen-Z in Greater Solo. However, Hedon Lifestyle is unable to moderate the relationship between Digital Financial Literacy and QRIS Usage Decision